Invasive round goby, Neogobius melanostomus - suitable prey for native cod, Gadus morhua? - Ljung, Andreas (2020)
Invasive species is a worldwide issue that is considered to be the one of the main reasons to losses of biodiversity. The round goby, Neogobius melanostomus, is an invasive species in the Baltic Sea that originates from the Black- and Caspian Sea. It was probably introduced via ballast water and since the discovery of the first speci-mens in 1990 round goby has spread and is now established along a majority of the Baltic coasts.